Perbedaan Hasil Belajar IPA Fisika antara Menggunakan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray dan Tipe Script - Lista M. Busula; Syamsu Syamsu (Universitas Tadulako, 2022)
This research was conducted with the aim of knowing whether there were differences in learning outcomes in Science Physics between students following the Two Stay Two Stray cooperative model and the Script type in class VIII SMP Negeri 7 Palu. This research is the quasi-experimental research with pretest-posttest design. The population in this study were students of class VIII SMP Negeri 7 Palu. The sample in this study was students of class VIII D as an experimental class 1 with 21 students and class VIII B as an experimental class 2 with 20 students. The post-test Science Physics learning results obtained showed that the average score of the experimental group 1 was 16.5 and the experimental group 2 was 12.15 for an ideal score of 20 and the standard deviation of experiment 1 was 4.56 and experiment 2 was 3.95. Test the hypothesis t test (two parties) at a significant level α = 0.05 and degree of wettability, dk = 39 where t0.975(39) = 2.02 and tcount = 3.27 with criteria H0 is accepted if –t (1-1/2α) < t < t(1-1/2α). So, it can be seen that the value of tcount is in the area of rejection of H0, thus H1 is accepted. It was concluded that there were differences in learning outcomes in Science Physics between students who participated in cooperative learning of the Two Stay Two Stray type and the Script type.